The Sōtō Sect and Japanese Military Imperialism in Korea - Hur, Nam-lin (Japanese journal of religious studies, 1999)
The Sōtō sect was actively engaged in Buddhist propagation in colonial Korea after having succeeded in establishing its first missionary temple in Pusan in 1905. By the time it withdrew from Korea in 1945, the Sōtō sect had secured an extensive propagation network connecting more than one hundred temples. Despite its successful Buddhist polemics, Sōtō's Buddhist teachings in Korea were basically political propaganda viable only within the framework of Japanese colonial imperialism. The Sōtō sect in colonial Korea was deeply involved in the cause of Japanese imperialism by carrying out three major tasks: Buddhist services for the Japanese military, promotion of the "kōminka" (transforming [the colonial peoples] into imperial subjects) policy, and the pacification of colonial subjects. Not surprisingly, none of these goals-which were promoted in the name of Buddhist compassion and non-selfhood in the tradition of Zen Buddhism-could survive the collapse of Imperial Japan's claim to "universal benevolence" that had been premised on the Greater East Asia Coprosperity Sphere.